On a class of quasilinear elliptic problems with critical exponential growth on the whole space - de Oliveira, José Francisco (Topological Methods in Nonlinear Analysis, 2016)
In this paper we prove a kind of weighted Trudinger-Moser inequality which is employed to establish sufficient conditions for the existence of solutions to a large class of quasilinear elliptic differential equations with critical exponential growth. The class of operators considered includes, as particular cases, the Laplace, p-Laplace and k-Hessian operators when acting on radially symmetric functions.